The Effect of Mechanical and Geometric Parameters on the Shear and Axial Failures of Columns in Reinforced Concrete Frames - Farahmand, Hooman; Kakavand, Mohammad Reza Azadi; Tafreshi, Shahriar Tavousi; Hafiz, Pooria Hafiz (Ciência e Natura, 2015)
Experimental research activities and post-earthquake considerations have demonstrated that reinforcedconcrete columns with light or widely spaced transverse reinforcement are vulnerable to shear failure duringearthquakes. According to this point by using failure limit curve, we can assess the effective parameters in shearand axial failure of reinforced concrete columns in framed buildings. In the current study by flexural, shear andaxial springs which are used in series, shear and axial failures and important effective parameters have beenassessed, Besides 5,10 and 15 story models with different amounts of initial axial load ratio have been analyzedby nonlinear push-over analysis. The results of analytical models contain behavior of buildings based on differentinitial axial load ratio and different spacing of transverse reinforcement are compared